Te Whakakāinga Haere i Te Mana o Ngā Taonga Tuku Iho o Ngāti Mākoro - Tipuna, Poihakena Wiremu (Auckland University of Technology, 2014)
This thesis examines the relationship that the whānau (family) Tipuna, of the hapū (sub-tribe) Ngāti Mākoro, Whetu Mārama Marae, which is of the iwi (people) Ngāti Kahungunu ki te Wairoa, has with their social cultural knowledge. This study examines the whānau Tipuna social-cultural practices, which reflect the processes of inter-generational knowledge transmission. These inter-generational knowledge transmission mechanisms provide a template to the practical application of Ngāti Mākoro processes pertaining to the art of toitoi tuna, toi tuna, hī tuna (eel bobbing, eel fishing). An indigenous framework of inter-generational knowledge transmission, using Māori metaphoric symbols and the history of a whakatauākī (proverbial saying of which the author is known) attributed to Tama-te-rangi is developed to provide an understanding into the thinking processes of our tīpuna (ancestors). This thesis will assist Ngāti Mākoro descendants with their understanding of the important responsibility they have to look after the knowledge of their tīpuna (ancestors). A kaupapa (theme) Māori research methodology is used as it reflects Māori philosophical investigative skills, values, beliefs and knowledge. The methodology for this study will be interactive in terms of the tuna fishing practices shared in and experienced within the whānau from the researcher’s perspective, as a participant observer not just an observer. Ngāti Mākoro epistemology will also be included in the methodology when researching Ngāti Mākoro tuna fishing practices. The validation of Ngāti Mākoro ways of thinking will provide for the whānau the endorsement to their young people that the knowledge thinking processes of their tīpuna has the ability to hold its own status in the world of academic knowledge.
Keywords: Inter-generational Knowledge Transmision; Encouraging participation of Māori social cultural tikanga (custom) practices